Motivations to Act for the Protection of Nature Biodiversity and the Environment: A Matter of "Significance". Issue 10 (December 2020) - Molinario, Erica; Kruglanski, Arie W.; Bonaiuto, Flavia; Bonnes, Mirilia; Cicero, Lavinia; Fornara, Ferdinando; Scopelliti, Massimiliano; Admiraal, Jeroen; Beringer, Almut; Dedeurwaerdere, Tom; deGroot, Wouter; Hiedanpää, Juha; et al.
Environmental activism, defined as a range of difficult pro-environmental behaviors, is analyzed within the conceptual framework of Significance Quest Theory (SQT). In Study 1, 40 interviews were carried out on two groups of people in the European Union: Committed Actors for Nature (CANs, n = 25) versus Committed Actors for Society (CASs, n = 15). Results demonstrated that Significance Quest (SQ) motivates each group to be strongly committed to their chosen action and the main difference between them being in their ideology (pro-social vs. pro-environmental). In Study 2 ( N = 131), the relationship between SQ and intention to enact difficult pro-environmental behaviors was assessed. Results suggested that the higher the SQ, the higher the tendency to enact difficult pro-environmental behaviors, but not average or easy ones. Moreover, the higher the pro-environmental ideology, the stronger the indirect effect of SQ on difficult behavior through willingness to sacrifice.